2002
DOI: 10.1038/sj.bjc.6600536
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylgalactosaminyl transferase-3 is a potential new marker for non-small cell lung cancers

Abstract: N-acetylgalactosaminyl transferase-3 (GalNAc-T3) is an enzyme involved in the initial glycosylation of mucin-type O-linked proteins. In the present study, we used immunohistochemistry to examine GalNAc-T3 expression in 215 surgically resected non-small cell lung cancers. We analysed the biological and clinical importance of GalNAc-T3 expression, especially with regard to its potential as a prognostic factor. We found that normal bronchial epithelial cells, bronchial gland cells, and alveolar pneumocytes showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 20 publications
(20 reference statements)
4
32
0
Order By: Relevance
“…In the adenocarcinomas of some organs, including the pancreas and gallbladder, the presence of weak expression or diffuse-type GalNAc-T3 expression in EBDCs T Inoue et al localization of GalNAc-T3 was correlated with tumor aggressiveness. [24][25][26][27][28][29] On the other hand, early-stage gastric carcinomas with submucosal invasion tended to show positive (strong or granular) GalNAc-T3 expression, while early-stage undifferentiated gastric carcinomas showing positive GalNAc-T3 expression were associated with significantly higher frequencies of metastatic lymph node involvement. 30 In addition, GalNAc-T3-positive esophageal squamous cell carcinomas exhibited more aggressive behavior.…”
Section: Galnac-t3 Expression In Ebdcs T Inoue Et Almentioning
confidence: 88%
See 2 more Smart Citations
“…In the adenocarcinomas of some organs, including the pancreas and gallbladder, the presence of weak expression or diffuse-type GalNAc-T3 expression in EBDCs T Inoue et al localization of GalNAc-T3 was correlated with tumor aggressiveness. [24][25][26][27][28][29] On the other hand, early-stage gastric carcinomas with submucosal invasion tended to show positive (strong or granular) GalNAc-T3 expression, while early-stage undifferentiated gastric carcinomas showing positive GalNAc-T3 expression were associated with significantly higher frequencies of metastatic lymph node involvement. 30 In addition, GalNAc-T3-positive esophageal squamous cell carcinomas exhibited more aggressive behavior.…”
Section: Galnac-t3 Expression In Ebdcs T Inoue Et Almentioning
confidence: 88%
“…Although most previous studies evaluating GalNAc-T3 expression by immunohistochemistry have divided the observed expression patterns into high-intensity (strong, positive) and low-intensity (weak, negative) groups, [24][25][26][27][28]30,31 Miyahara et al 29 divided the GalNAc-T3 expression patterns of gallbladder carcinomas into granular and diffuse types, mostly corresponding to highintensity and low-intensity expression, respectively. We also found that the immunohistochemical staining of GalNAc-T3 in EBDCs showed granulartype and diffuse-type expression patterns, and these features of EBDCs were similar to those reported for gallbladder adenocarcinomas.…”
Section: Galnac-t3 Expression In Ebdcsmentioning
confidence: 99%
See 1 more Smart Citation
“…The labeled streptavidin biotin method was used on 4-m sections of formalin-fixed, paraffinembedded tissues after deparaffinization. The primary antibodies used were a mouse monoclonal MIB-1 antibody (Immunotech, Marseilles, France), a mouse monoclonal antihuman p27 KIP1 antibody (clone 1B4; Novocastra, Newcastle, United Kingdom), a mouse monoclonal antihuman cyclin E antibody (HE12; PharMingen, San Diego, CA), and a rabbit polyclonal antibody against a synthesized peptide of human GalNAc-T3 (21).…”
Section: Tumormentioning
confidence: 99%
“…Risk of epithelial ovarian cancer (8) and coronary artery disease (9) have been associated with single nucleotide polymorphisms of GALNT1 and GALNT2, respectively. GALNT3 expression is a potential diagnostic marker for lung (10) and pancreatic (11) cancers. GALNT6 modifies mucin 1 glycosylation and regulates proliferation of breast cancer cells (12).…”
Section: Introductionmentioning
confidence: 99%